2004
DOI: 10.1111/j.1365-2362.2004.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia and sinus arrest during percutaneous ethanol injection therapy for hepatocellular carcinoma

Abstract: Bradycardia and block formation occur frequently during PEI. These symptoms could be explained by a vasovagal reaction and/or the direct effect of ethanol on the sinus node or the right atrial conduction system. Ethanol dose is an important factor for the occurrence of SAB/AVB. ECG-monitoring seems mandatory during PEI. Prophylactic use of intravenously administered Atropine might be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Although uncommon, bradycardia and heart block have been linked to cisplatin, irinotecan, paclitaxel, mitoxantrone (and rarely, doxorubicin), octreotide, thalidomide, methotrexate, 5-fluorouracil, and arsenic trioxide (61,73). Ethanol, which is injected percutaneously for treatment of hepatocellular carcinoma, can cause sinus bradycardia and heart block (122). …”
Section: Arrhythmiasmentioning
confidence: 99%
“…Although uncommon, bradycardia and heart block have been linked to cisplatin, irinotecan, paclitaxel, mitoxantrone (and rarely, doxorubicin), octreotide, thalidomide, methotrexate, 5-fluorouracil, and arsenic trioxide (61,73). Ethanol, which is injected percutaneously for treatment of hepatocellular carcinoma, can cause sinus bradycardia and heart block (122). …”
Section: Arrhythmiasmentioning
confidence: 99%
“…Quite frequently, complications related to cardiac bradyarrhythmias are observed, sometimes with clinical consequences such as respiratory or haemodynamic impairment (6). In a previous study by our own group, these dysrhythmias were recognized in up to 25% of patients receiving PEI (7). We noticed two severe clinical incidents during PEI.…”
mentioning
confidence: 77%
“…Ferlitsh et al 4 reported a sinoatrial and atrio-ventricular block in patients with SVH following ethanol injection. Another mechanism of circulatory depression, an acute increase in pulmonary vascular resistance causing right ventricular dysfunction that can precipitate cor pulmonale in susceptible individuals, has also been suggested.…”
Section: Discussionmentioning
confidence: 98%